1999
DOI: 10.1007/s100510050958
|View full text |Cite
|
Sign up to set email alerts
|

Eden growth model for aggregation of charged particles

Abstract: The stochastic Eden model of charged particles aggregation in two-dimensional systems is presented. This model is governed by two parameters: screening length of electrostatic interaction, $\lambda $, and short range attraction energy, $E$. Different patterns of finite and infinite aggregates are observed. They are of following types of morphologies: linear or linear with bending, warm-like, DBM (dense-branching morphology), DBM with nucleus, and compact Eden-like. The transition between the different modes of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Ivanenko (Ivanenko, Lebovka et al 1999) found that reaction limited agglomeration occurs between particles and clusters of the same charge. Since charged particles repel each other, only particles colliding with adequate energy to overcome the electrostatic barrier agglomerate.…”
Section: Large Particle Generationmentioning
confidence: 99%
“…Ivanenko (Ivanenko, Lebovka et al 1999) found that reaction limited agglomeration occurs between particles and clusters of the same charge. Since charged particles repel each other, only particles colliding with adequate energy to overcome the electrostatic barrier agglomerate.…”
Section: Large Particle Generationmentioning
confidence: 99%
“…In view of the encountered analogies between the MEM and the Ising model, it is natural to test the validity of equations (14)(15)(16)(17) for the case of the MEM in (2 + 1)-dimensions. It should be noted that as in the case of equilibrium systems, in the present case various "effective" L-dependent critical temperatures can also be defined.…”
Section: Order-disorder Phase Transition In the (2+1)-dimensionalmentioning
confidence: 99%
“…Hence, all cell activities are directed towards finding an available site with sufficient nutrient supply for the adhesion. Cell deposition onto the surface occurs by the mechanism similar to that of a diffusion-limited aggregation [10] process. Characteristic time of cell deposition is significantly shorter than the characteristic reproduction time of the bacteria.…”
Section: Model Of Biofilm Development In Batch Reactormentioning
confidence: 98%